2009
DOI: 10.1158/0008-5472.can-08-1189
|View full text |Cite
|
Sign up to set email alerts
|

p34SEI-1 Inhibits Apoptosis through the Stabilization of the X-Linked Inhibitor of Apoptosis Protein: p34SEI-1 as a Novel Target for Anti–Breast Cancer Strategies

Abstract: The p34SEI-1 protein exerts oncogenic effects via regulation of the cell cycle, which occurs through a direct interaction with cyclin-dependent kinase 4. Such regulation can increase the survival of various types of tumor cells. Here, we show that the antiapoptotic function of p34 SEI-1 increases tumor cell survival by protecting the X-linked inhibitor of apoptosis protein (XIAP) from degradation. Our findings show that p34 inhibits apoptosis. This antiapoptotic effect was eliminated by the suppression of p34… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 22 publications
3
77
0
Order By: Relevance
“…A recent study found that p34 SEI1 could inhibit apoptosis through the stabilization of the X-linked inhibitor of apoptosis protein (13). Our previous study indicated that the oncogenic function of SEI1 was associated with chromosome instability (14).…”
Section: Introductionmentioning
confidence: 94%
“…A recent study found that p34 SEI1 could inhibit apoptosis through the stabilization of the X-linked inhibitor of apoptosis protein (13). Our previous study indicated that the oncogenic function of SEI1 was associated with chromosome instability (14).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we reported that human breast cancer cells display different sensitivities to various stimuli, including staurosporine, etoposide and cisplatin, depending on their level of p34 SEI-1 protein. 14 On the basis of these results, we tested the p34 SEI-1 dependence of the sensitivities of human colon cancer cells to the cytotoxic stressor H 2 O 2 , which can induce cell death through an increase in intracellular ROS levels.…”
Section: P34mentioning
confidence: 99%
“…Total cell proteins (20 μg) were resolved by sodium dodecylsulfate-PAGE (SDS-PAGE) and transferred to PolyScreen membranes (New England Nuclear, Boston, MA). Membranes were blocked with 5% non-fat dry milk in Tris-buffered saline containing 0.1% Tween-20 (TBS-T), 14 and probed with primary antibodies against p34 (Axxora LLC, San Diego, CA), ASK1, HA, GFP, anti-γ-tubulin (Santa Cruz Biotechnology, Santa Cruz, CA), and/or phospho-ASK1 (Cell Signaling Technology, Beverly, MA). Primary antibodies were detected with horseradish peroxidase-conjugated goat anti-mouse, goat anti-rabbit or donkey anti-goat secondary antibody, as appropriate and proteins were visualized using an enhanced chemiluminescence system (Amersham, Buckinghamshire, UK).…”
Section: Cell Viability Analysis Control Cells or Cells Expressing Amentioning
confidence: 99%
“…20,21 p34 amplification has been observed in various human carcinomas, including pancreatic, 22 lung, 23 and ovarian cancers. 24 p34 was recently reported to be strongly expressed in human breast cancer tissues but was absent or weakly expressed in normal tissues, 25 implying that p34 may be an oncoprotein. We found that p34 (SEI-1) directly interacts with the WW1 domain of NEDD4-1, whereas its close homologs, SEI-2 and SEI-3, do not (data not shown).…”
mentioning
confidence: 99%
“…Consistent with this observation, NEDD4-1 potentiates oncogenic Ras-induced cell transformation in a PTENdependent manner, suggesting that aberrant upregulation of NEDD4-1 can suppress PTEN in human cancers. 12,16,25 The finding that NEDD4-1 is an E3 ubiquitin ligase for PTEN raises a very important question: How is NEDD4-1 regulated? Moreover, what factors are intimately involved in the NEDD4-1-mediated degradation of PTEN?…”
mentioning
confidence: 99%